Proceedings of the 2006 20th Anniversary Conference on Computer Supported Cooperative Work 2006
DOI: 10.1145/1180875.1180914
|View full text |Cite
|
Sign up to set email alerts
|

The uses of paper in commercial airline flight operations

Abstract: Designers of commercial aviation flight decks have recently begun to consider ways to reduce or eliminate the use of paper documents in flight operations. Using ethnographic methods we describe the cognitive functions served by the paper-use practices of pilots. The special characteristics of flight deck work give a distinctive quality to pilots' paper-use practices. The complex high-stakes high-tempo nature of pilots' work makes shared understandings essential to safe flight. This means that representation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 18 publications
1
20
0
1
Order By: Relevance
“…Research is needed to better understand how such changes in concept of operations can be effectively managed without compromising safety. Similar research has been suggested in the aviation domain (Nomura, Hutchins, & Holder, 2009).…”
Section: A12 Transitioning To Cbp Systems From a Pbp Operational Envsupporting
confidence: 82%
“…Research is needed to better understand how such changes in concept of operations can be effectively managed without compromising safety. Similar research has been suggested in the aviation domain (Nomura, Hutchins, & Holder, 2009).…”
Section: A12 Transitioning To Cbp Systems From a Pbp Operational Envsupporting
confidence: 82%
“…For example, the paperuse practices of pilots serve a set of important cognitive functions such as managing the allocation of attention (Nomura et al, 2006). In a newspaper office, physical artefacts represent tokens of responsibility (Bellotti and Rogers, 1997).…”
Section: The Significance Of Physicalitymentioning
confidence: 99%
“…Hence paper-based information documents often have to be physically moved between locations where and when they are needed. While paper documents afford valuable benefits in viewing, reviewing, customizing, annotating, carrying, and amending data [8,16,18], they often fall short in providing timely, locationindependent and simultaneous multiple information access. Therefore, in reality, required information may not be available at the right place and/or at the right time since tedious, sometimes complex, administrative policies, procedures, and coordination often impedes the physical delivery of paper information documents [8].…”
Section: Related Workmentioning
confidence: 99%